A National Survey of Community Pharmacists’ Viewpoints About Pharmacovigilance and Adverse Drug Reaction Reporting in Saudi Arabia - Alsheikh, Mona Y.; Alasmari, Moudi M. (Frontiers in Pharmacology, 2022)
This study assessed the knowledge, attitudes, and practices of community pharmacists regarding the pharmacovigilance and adverse drug reaction (ADR) reporting system in Saudi Arabia. A cross-sectional survey of community pharmacists from different regions in Saudi Arabia was performed through convenience sampling between November 2020 and January 2021. The responses were received from 1,172 community pharmacists. Most respondents (86.7%) were familiar with the National Pharmacovigilance and Drug Safety Center, and 830 (70.8%) knew about the ADR reporting form. The majority (94%) of the respondents agreed with the importance of reporting ADRs for patient care and national health. Although 92.2% of the participants asked their patients about ADRs, 90.2% agreed that more training programs need to be organized by the Saudi Food and Drug Authority for healthcare professionals on ADR detection and reporting system. Analgesic agents were the most common drug category for which ADRs were reported (67.4%). The majority (92.1%) of ADRs reported occurred in patients with chronic diseases. The study concluded that most community pharmacists in Saudi Arabia are knowledgeable and have good attitudes and practices regarding pharmacovigilance and ADR reporting.